2009
DOI: 10.1111/j.1365-2788.2008.01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical mobility limitations in adults with intellectual disabilities: a systematic review

Abstract: Background Mobility limitations increase with age in the general population. Despite a growing population of older adults with intellectual disabilities (ID), mobility is rarely studied in the ID literature. The specific aim of this study was to identify and summarise primary literature investigating mobility limitations in adults with ID. Methods This study was a systematic review of the epidemiological literature (incidence and prevalence) of mobility limitations among adults with ID. Four electronic databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 56 publications
3
49
0
Order By: Relevance
“…Intellectual disabilities negatively affect the life of a person with disability also by decreasing their motor function, which is manifested by poor visual and motor coordination, limited precision of movements, inhibition, and difficulties in learning new forms of activities2, 3 ) . Alongside impairments in cognitive and motor function, individuals with intellectual disability also have lower levels of physical fitness at all stages of life due to inactive ways of life1, 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Intellectual disabilities negatively affect the life of a person with disability also by decreasing their motor function, which is manifested by poor visual and motor coordination, limited precision of movements, inhibition, and difficulties in learning new forms of activities2, 3 ) . Alongside impairments in cognitive and motor function, individuals with intellectual disability also have lower levels of physical fitness at all stages of life due to inactive ways of life1, 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…(2) During the process of physiological aging, changes such as loss of muscle mass and reduction in strength and muscle function, joint stiffness and reduced range of motion, alterations in gait and in balance may significantly compromise the physical mobility of the elderly, predisposing them to falls, pain and functional disability. (3) It is noteworthy that several risk factors may be associated with mobility limitations in the elderly, and these can be individual, social, environmental and organizational.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that people with ID have rather heterogeneous motor behavior (Cleaver et al 2009), it would be quite safe to state that they are in general slower and more "clumsy," and they tend to require more time during motor learning processes compared to their nondisabled counterparts (Davis and Van Emmerik 1995). Studies indicated that children with ID are retarded by 2-4 years in most motor tasks (Rarick et al 1970).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason limitations in mobility, reflected in gait and balance deficits, may be common in people with ID, ranging from 3 to 63 % depending on the sample characteristics (prevalence of other disabilities, age, gender, level of ID, etc.) and the definition of mobility vs. impaired mobility (Cleaver et al 2009). …”
Section: Introductionmentioning
confidence: 99%